Facial Recognition Shuffle Keypad for Secure ATM Transactions - Kumar, Thamada Ram; Srinivas, V. Naga; Ali, Md. Basheer; Pravalika, S. (International Journal of Research in Interdisciplinary Studies, 2025)
Over the past decade, a worrisome surge in ATM extortion has spurred innovation in security measures. Enter a groundbreaking project: a system that revolutionizes ATM transactions by replacing traditional cards and PINs with advanced biometric validation and facial recognition technology. No more fumbling for cards or trying to recall PINs; this system simplifies and fortifies the process. Imagine this: you approach the ATM, and instead of reaching for your wallet, you simply present your face to the scanner. Instantly, the system verifies your identity, distinguishing between the real you and any impostors. But the security doesn't stop there. To add an extra layer of protection, a unique 6-digit OTP is generated and sent to your registered mobile number via SMS. With the valid OTP entered, you're granted access to a plethora of banking options. And should any suspicious activity occur, rest assured that you'll be promptly alerted. This innovative approach not only enhances security but also streamlines the transaction process, making your ATM experience safer and more seamless than ever before.